2000
DOI: 10.1002/(sici)1097-0134(20000601)39:4<331::aid-prot60>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of polar residues as hot spots at protein interfaces

Abstract: A number of studies have addressed the question of which are the critical residues at protein-binding sites. These studies examined either a single or a few protein-protein interfaces. The most extensive study to date has been an analysis of alanine-scanning mutagenesis. However, although the total number of mutations was large, the number of protein interfaces was small, with some of the interfaces closely related. Here we show that although overall binding sites are hydrophobic, they are studded with specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 16 publications
1
68
0
Order By: Relevance
“…Incorporated into proteins, Arg is important for recognizing anionic biological entities such as phosphates (Hirsch et al 2007), glycosaminoglycans (Blaum et al 2010), and others (Chakrabarti 1994). Furthermore, Arg is responsible for the cell penetration activity of Arg-containing proteins/peptides (Wender et al 2000(Wender et al , 2008Mitchell et al 2000), and is frequently observed at protein-protein interaction interfaces and hotspots (Janin et al 1988;Argos 1988;Jones and Thornton 1995;Tsai et al 1997;Bogan and Thorn 1998;Hu et al 2000). For technological advantages, Arg derivatives have been covalently attached to carbohydrates to enhance the detection sensitivity of oligosaccharides in MALDI (matrix-assisted laser desorption ionization) mass spectrometry analysis (Zhao et al 1997;Shinohara et al 2004;Baumgart et al 2004;Nishikaze and Takayama 2006;Northern et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Incorporated into proteins, Arg is important for recognizing anionic biological entities such as phosphates (Hirsch et al 2007), glycosaminoglycans (Blaum et al 2010), and others (Chakrabarti 1994). Furthermore, Arg is responsible for the cell penetration activity of Arg-containing proteins/peptides (Wender et al 2000(Wender et al , 2008Mitchell et al 2000), and is frequently observed at protein-protein interaction interfaces and hotspots (Janin et al 1988;Argos 1988;Jones and Thornton 1995;Tsai et al 1997;Bogan and Thorn 1998;Hu et al 2000). For technological advantages, Arg derivatives have been covalently attached to carbohydrates to enhance the detection sensitivity of oligosaccharides in MALDI (matrix-assisted laser desorption ionization) mass spectrometry analysis (Zhao et al 1997;Shinohara et al 2004;Baumgart et al 2004;Nishikaze and Takayama 2006;Northern et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hotspots previously identified by alanine scanning had the strictest requirements for substitution, with the wild-type amino acid being most favorable [24]. This conclusion is supported by a meta-analysis of alanine-scanning data from the literature, which concluded that evolutionarily conserved residues at interfaces are more likely to be hotspots [25].…”
Section: Hotspots At Interfacesmentioning
confidence: 78%
“…In general, molecular recognition takes place as a result of a complex interplay of different noncovalent interactions established between the binding partners that, globally, need to overcome those established with the solvent in the unbound state. Nonetheless, the relative weight of each of the interacting forces might be different depending on the specific characteristics of the system (for example, electrostatic interactions seem to play a more important role in protein binding than in protein folding) [16,17]. A detailed description of the nature of noncovalent interactions and the experimental procedures available to estimate their strength and range can be found in [18][19][20].…”
Section: Intermolecular Forces In Protein Recognitionmentioning
confidence: 99%